2020
DOI: 10.1177/1057083720951462
|View full text |Cite
|
Sign up to set email alerts
|

Digital Natives Unplugged: Challenging Assumptions of Preservice Music Educators’ Technological Skills

Abstract: Generational labels such as digital native and the “net” generation may obscure the gap that exists between preservice music teachers’ personal uses of technology and how they will use technology professionally. The study’s purpose was to examine preservice music teachers’ personal use of technology, views toward technology in music teaching and learning, and experience with music technology. We distributed an online survey to collegiate members of the National Association for Music Education, with 360 undergr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In any case, I am careful not to assume that students will be familiar with these tools because they use computers or technology often and try to help as needed. 34…”
Section: Editingmentioning
confidence: 99%
“…In any case, I am careful not to assume that students will be familiar with these tools because they use computers or technology often and try to help as needed. 34…”
Section: Editingmentioning
confidence: 99%
“…As a result of the study, it was revealed that the technology-supported teaching-learning approach contributed positively to the creativity of the students, changed their musical perceptions and improved their musical creativity. Bannerman et al (2021) aimed to establish the personal technology use of music teacher candidates, their views on the use of technology in music teaching and their experiences with music technology. They concluded that music teacher candidates used technology for various purposes on a daily basis and did not feel knowledgeable about technology for teaching music.…”
Section: Introductionmentioning
confidence: 99%
“…The process of training future music teachers can be implemented with the help of SinophonicOnline, Musicca14, E-Book Maestro and other technologies (Bannerman & O'Leary, 2021). For example, the Sibelius application facilitates the study of sheet music, enabling the division of a piece of music for easier comprehension.…”
Section: Introductionmentioning
confidence: 99%